2020
DOI: 10.1007/s13143-020-00201-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China

Abstract: Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960-2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The normalized magnitude in Hong Kong was smaller than that in Taiwan. That was primarily due to the different terrains of Hong Kong and Taiwan (Bao et al., 2017; Wang et al., 2020; Yeh et al., 2016). The east coast of Taiwan is mountainous, which blocks most of PWV flux from the sea.…”
Section: Resultsmentioning
confidence: 99%
“…The normalized magnitude in Hong Kong was smaller than that in Taiwan. That was primarily due to the different terrains of Hong Kong and Taiwan (Bao et al., 2017; Wang et al., 2020; Yeh et al., 2016). The east coast of Taiwan is mountainous, which blocks most of PWV flux from the sea.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the PDF curve of Factors such as translation speed and intensity have a significant impact on TC precipitation [39,64,65]. Moreover, many studies have shown that the BTC effect causes the track of TCs to change irregularly and suddenly [23,26,27,29,32]. Therefore, we consider the translation speed (V = distance(P t+1 − P t−1 )/2t, where P t−1 and P t+1 represent the TC positions at the previous and next time steps, respectively), intensity, and direction change (∆θ = abs(θ t − θ t−1 ), where θ t = direction(P t − P t−1 ), θ t = 0 • , 90 moving eastward, northward, westward, and southward, respectively) as factors that may influence typhoon precipitation for diagnostic analysis.…”
Section: Rainfall Differences and Causes Of Ttc And Its Sim_tc For Na...mentioning
confidence: 99%
“…Tropical cyclones (TCs) are one of the severe weather systems, which often cause huge economic losses and casualties with extreme winds, storm surges, and/or torrential rainfall in the coastal regions and on some inlands (M. Wang et al., 2021; Yu, 2015). Accurate forecast of TC rainfall is necessary for management of fresh water resources and rainfall‐induced disaster warning system (Wu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…
Tropical cyclones (TCs) are one of the severe weather systems, which often cause huge economic losses and casualties with extreme winds, storm surges, and/or torrential rainfall in the coastal regions and on some inlands (M. Wang et al, 2021;Yu, 2015). Accurate forecast of TC rainfall is necessary for management of fresh water resources and rainfall-induced disaster warning system (Wu et al, 2018).In recent years, many progresses have been made in TC track forecasting, owing to the advancements in observational technology, numerical models and our understanding of underlying physics.
…”
mentioning
confidence: 99%